The effect of ZnO nanoparticles on the physical, mechanical, and antibacterial properties of chitosan/gelatin hydrogel films - Nurul Amira, Ahmad Yusof; Norashikin, Mat Zain (Penerbit Universiti Teknologi Malaysia, 2019)
Apart from biocompatibility, hydrogel films with good physical, morphology, swelling, and antibacterial properties are required for biomedical applications. In this study, the effects of nanofiller (i.e., zinc oxide (ZnO) nanoparticles) on physical, morphology, swelling, and antibacterial properties of hydrogel film were investigated. The new chitosan/gelatin/ZnO hydrogel films were synthesized using solution casting method by blending the chitosan and gelatin solutions with ZnO nanoparticles. The use of glycerol (plasticizing agent) could enhance the durability and flexibility of the hydrogel film. From the FTIR results, it was found that chemical reactions occurred of gelatin was between 1500 cm-1 to 800 cm-1. On the other hand, the SEM results showed that the pore size distribution within the hydrogel film varied from 20µm to 700µm. The antibacterial properties ZnO hydrogel film against bacteria such as Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) were evaluated using the zone of inhibition method. The antibacterial activity (against the S. aureus bacteria) of the new ZnO hydrogel film was more promising than that of the nanoparticle-free hydrogel film. The current findings showed that the new chitosan/gelatin/ZnO hydrogel film could be used in biomedical application.